Exposure–response analysis of acalabrutinib and its active metabolite, ACP‐5862, in patients with B‐cell malignancies. Issue 5 (17th October 2021) - Edlund, Helena; Buil‐Bruna, Núria; Vishwanathan, Karthick; Wei, Helen; Raman, Rakesh; de Kock, Miné; He, Zhongqing; Liu, Huan; Baek, Marshall; Ware, Joseph; Patel, Priti; Tomkinson, Helen; et al.
Abstract : Aims: Examine relationships between the systemic exposure of acalabrutinib, a highly selective, next‐generation Bruton tyrosine kinase inhibitor, and its active metabolite (ACP‐5862) vs . efficacy and safety responses in patients with B‐cell malignancies who received acalabrutinib as monotherapy or in combination with obinutuzumab. Methods: For exposure–efficacy analyses, patients with untreated chronic lymphocytic leukaemia were assessed for best overall response, progression‐free survival and tumour regression. For exposure–safety analyses, incidences of grade ≥2 adverse events (AEs), grade ≥3 AEs and grade ≥2 events of clinical interest were assessed in patients with B‐cell malignancies. Acalabrutinib and ACP‐5862 pharmacokinetic (PK) parameter estimates were obtained from population PK modelling. Exposure calculations were based on study dosing regimens. Total active moieties were calculated to account for contributions of ACP‐5862 to overall efficacy/safety. Results: A total of 573 patients were included (exposure–efficacy analyses, n = 274; exposure–safety analyses, n = 573). Most patients (93%) received acalabrutinib 100 mg twice daily. Median total active area under the concentration–time curve (AUC24h, ss ) and total active maximal concentration at steady‐state (Cmax, ss ) were similar for patients who received acalabrutinib as monotherapy or in combination with obinutuzumab, and for responders and nonresponders. No relationship was observed between AUC24h, ss /Cmax, ss and progression‐free survival or tumour regression. Acalabrutinib AUC24h, ss and Cmax, ss were generally comparable across groups regardless of AE incidence. Conclusion: No clinically meaningful correlations between acalabrutinib PK exposure and efficacy and safety outcomes were observed. These data support the fixed acalabrutinib dose of 100 mg twice daily in the treatment of patients with B‐cell malignancies.